Technological Development, Knowledge, Attitude and the Use of ChatGPT in the Learning Method of Higher Education Students - Alya Athirah Aziz; Fatin Nur Aisyah Zulkapli; Iffah Mawaddah Mohd Helme; Jasslina Md Zamsari; Nurhazwanie Hashim; Siti Yuliandi Binti Ahmad (Jurnal Audiens, 2024)
This study aims to understand the use of ChatGPT in the learning method, to measure the level of technological development, knowledge, attitude and the use of ChatGPT in the learning method, and to investigate the relationship between technological development, knowledge, attitude and the use of ChatGPT in the learning method of students at the university. The study was conducted using mixed methods, which are qualitative and quantitative. Five students were interviewed as participants for the qualitative method, and 36 responded to the survey. The data was analysed using Thematic Analysis for the interview data and descriptive analysis for the survey. The findings show that the highest mean is technological development, knowledge, and attitude. Findings from this study may serve as a basis for future researchers to analyse other variables in using ChatGPT in the learning method among the more extensive community.